Implementation, Socialization and Marketing of Processed Moringa Plant Products as An Effort to Improve Community Health - Pratamaningtyas, Susanti; Titisari, Ira; Rahmawati, Rahajeng Siti Nur (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2022)
Accelerating the reduction of stunting is the government's focus in the health sector. However, the COVID-19 pandemic is one of the obstacles. Besides affecting health conditions in Indonesia, the pandemic also has an impact on the family economy, making it even more difficult to implement stunting prevention. So in this case, the community service team wants to provide education and training on the use of surrounding natural resources into nutrient-dense and selling-value food, especially in Bandar Lor village, which has the highest stunting incidence rate in Kediri city. Moringa leaves were chosen because, in addition to being dubbed as a superfood, Moringa leaves are safe to be consumed by children and pregnant women. Moringa leaves were processed into a mixture of soya milk, brownies, and nuggets which children like. During the training, participants seemed very enthusiastic about following the directions. It is hoped that this activity can help the community in processing the surrounding natural resources into nutrient-dense food as an effort to prevent stunting and also can become a new selling idea for a better economy.